Not the Crime but the Cover-Up: A Deterrence-Based Rationale for the Premeditation-Deliberation Formula - Mannheimer, Michael J. Zydney (2011)
Beginning with Pennsylvania in 1794, most American jurisdictions have, at one time or another, separated the crime of murder into two degrees based on the presence or absence of premeditation and deliberation. An intentional, premeditated, and deliberate murder is murder of the first degree, while second-degree murder is committed intentionally but without premeditation or deliberation. The distinction was created in order to limit the use of the death penalty, which generally has been imposed only for first-degree murder. Critics have attacked the premeditation-deliberation formula on two fronts. First, they have charged that the formula is imprecise as a measure of the relative culpability or dangerousness of intentional murderers. The premeditation deliberation formula, the critics tell us, is incapable of segregating out the worst murderers because it is both under- and over-inclusive. In addition, critics have pointed to the courts’ inability or unwillingness to apply the premeditation deliberation formula in any coherent fashion. Many courts have held that the premeditation and deliberation required to transform a mere intentional, second-degree murder into first-degree murder can be formed in the instant before the killing. Thus do many courts fail to meaningfully distinguish one degree of intentional murder from the other. This second failing appears inextricably related to the first: since many unplanned but intentional murders are as bad as or worse than many planned killings, and their perpetrators at least as dangerous, courts contort the meanings of premeditation and deliberation to allow the most culpable and dangerous murderers to be punished most harshly. These criticisms are founded on the premise that the distinction between first and second-degree murder is grounded solely upon principles of retribution and incapacitation. What the critics have overlooked is that there is a powerful deterrence-based rationale for distinguishing premeditated, deliberate murders from those that are unpremeditated or nondeliberate. Where a murder is premeditated and deliberate, it is much more likely that the murderer has not only planned out the crime itself but has developed a plausible way to avoid or delay detection. Because the value of punishment as a deterrent depends in large part on the likelihood and swiftness of punishment, crimes that are less likely to be punished swiftly, all other things being equal, ought to be punished more severely. Thus, given two equally dangerous and culpable intentional murderers, we are arguably justified in punishing more severely the one who, by virtue of better planning beforehand, is more likely to escape or delay detection